Rapid and Sensitive Detection of an Intracellular Pathogen in Human Peripheral Leukocytes with Hybridizing Magnetic Relaxation Nanosensors - Kaittanis, Charalambos; Boukhriss, Hamza; Santra, Santimukul; Naser, Saleh A.; Perez, J. Manuel (PLOS ONE, 2012)
Bacterial infections are still a major global healthcare problem. The quick and sensitive detection of pathogens responsible for these infections would facilitate correct diagnosis of the disease and expedite treatment. Of major importance are intracellular slow-growing pathogens that reside within peripheral leukocytes, evading recognition by the immune system and detection by traditional culture methods. Herein, we report the use of hybridizing magnetic nanosensors (hMRS) for the detection of an intracellular pathogen, Mycobacterium avium spp. paratuberculosis (MAP). The hMRS are designed to bind to a unique genomic sequence found in the MAP genome, causing significant changes in the sample’s magnetic resonance signal. Clinically relevant samples, including tissue and blood, were screened with hMRS and results were compared with traditional PCR analysis. Within less than an hour, the hMRS identified MAP-positive samples in a library of laboratory cultures, clinical isolates, blood and homogenized tissues. Comparison of the hMRS with culture methods in terms of prediction of disease state revealed that the hMRS outperformed established culture methods, while being significantly faster (1 hour vs 12 weeks). Additionally, using a single instrument and one nanoparticle preparation we were able to detect the intracellular bacterial target in clinical samples at the genomic and epitope levels. Overall, since the nanoparticles are robust in diverse environmental settings and substantially more affordable than PCR enzymes, the potential clinical and field-based use of hMRS in the multiplexed identification of microbial pathogens and other disease-related biomarkers via a single, deployable instrument in clinical and complex environmental samples is foreseen.